Penggunaan Metode Peer Teaching Dalam Pembelajaran Gitar dan Keyboard di Gereja Toraja Jemaat Gandangbatu Timur Klasis Gandangbatu - Musa Masing (Clef: Jurnal Musik dan Pendidikan Musik, 2021)
Peer Teaching is a learning process by involving peers. The learning process can apply to any type of activity, including learning music. Peer Teaching in most churches did not develop this and chose to seek outside coaches rather than empowering church youth with great potential. The purpose of this study was to describe the Peer Teaching method in learning music (guitar and keyboard) which was carried out in the Gandangbatu Timur Congregation, Klasis Gandangbatu. Subjects in this study were 10 youths who were divided into 2 groups, namely the Music Guitar Group and the Music Keyboard Group. The method used in this research is a qualitative research method with a descriptive approach. The results showed that the music learning process using the Peer Teaching method was carried out by starting the basic concepts in music. The output of this Peer Teaching is the training of church youths who can serve in the congregation (Music Section)